Le Petit Rosaire (1600)
This is a seventeenth-century copy of a fifteenth-century translation and re-working of the Rosarius Philosophorum, one of the most important texts in the corpus of alchemical works that circulated under the name of Arnald of Villanova (c.1240-1311). Villanova was a Catalan physician; his authentic writings include important medical treatises, as well as numerous works of theology. His ties with the spiritual Franciscans and beliefs concerning the imminent coming of the Antichrist led to the condemnation of his writings by the theology faculty of the University of Paris. The work is extant in only two known copies. This particular copy is notable for its detailed illustrations of alchemical equipment and contemporary marginal notes; there are ninety-four pen-and-ink drawings added to spaces left blank by the scribe and introduced by captions. Blank spaces for drawings never completed are found on three folios. The illustrations likely depict actual contemporary alchemical equipment due to the care and realistic detail with which they have been rendered. The work is bound in contemporary limp vellum stretched over pasteboard. The smooth spine is inscribed with a title in ink, “Petit Rosaire d’Arnaud de Villeneuve.” Rubbed, darkened and slightly soiled, ties missing, covering at top and bottom corners and bottom of spine slightly damaged. Work is digitized in its entirety.
Keywords: Arnaldus, de Villanova, -1311; Alchemy; Alchemy--Manuscripts; Scientific apparatus and instruments; Scientific illustration